Can We Save the Implant: Rib-based Implant Removal Rates and Risk Factors Following Irrigation and Debridement (I&D) Surgery?. Issue 5 (27th May 2020) - Lott, Carina; Qiu, Catherine; McNeely, Lia W.; Galagedera, Nirupa; Campbell, Robert M.; Flynn, John M.; Cahill, Patrick J.; Anari, Jason B.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: In the event of a surgical site infection, management includes surgical debridement in an attempt to treat the infection and retain the implant; however they are often unsuccessful in this regard. Although studies have described the incidence of complications, current literature does not have sufficient evidence to provide clear recommendations regarding retention versus removal of implants. This study aims to identify predictive factors associated with the need for implant removal to decrease unnecessary attempts at implant retention. Methods: A retrospective review of early-onset scoliosis patients at a single institution treated with rib-based vertical expandable prosthetic titanium rib implants who developed infection requiring irrigation and debridement (I&D) due to wound problems including surgical site infection, skin slough, and wound dehiscence. All patients had a minimum of a 2-year follow-up. Univariate and multivariate logistic regression analyses were conducted to determine the odds of implant removal. Results: Fifty-nine of 181 patients (32%) required an I&D due to a wound problem. These patients underwent the initial implant procedure at a mean age of 4.6±3.8 years. In total, 29 patients ultimately underwent implant removal. Significant predictive factors for removal included total number of wound problems, total number of I&Ds, days from identification of wound problem to I&D procedure, days on antibiotics, total number of surgeries, presence of gastrostomy tube, and nonambulatory status ( P <0.0001, 0.001, 0.095, 0.093, 0.082, 0.054, and 0.026, respectively). Multiple logistic regression results indicated a total number of wound problems [odds ratio (OR): 6.00, P =0.001], average days from identification of wound problem to I&D (OR: 1.03, P =0.039), and presence of a gastrostomy tube (OR: 5.7, P =0.07) as independent predictors for implant removal. Conclusions: Data suggests that time from the onset of signs of infection until debridement surgery inversely correlates with the ability to retain the implants. In addition, gastrostomy tube and history of previous wound infections may be predictive clinical factors for implant removal in patients with a rib-based vertical expandable prosthetic titanium rib instrumentation. Such information can be useful for clinicians in deciding on whom to attempt implant retention versus removal when a wound problem presents itself. Level of Evidence: Level III.